WASTEWATER TREATMENT CENTER BENEFIT OF OR SLAUGHTER OF LIVESTOCK - Salas C., Gilberto (2008)
The meat processing industry is believed to produce highly polluted wastewater. Analysis of such wastewater indicated that the waste was highly contaminated with organic compounds as indicated by DQO (mg/L), DBO (mg/L ), and TSS (mg/L ). Moreover, oil and grease concentrations reached mg/L treatment of raw wastewater using Dissolved Air Flotation (DAF) was studied. Efficiency of the DAF for the removal of DBO, DQO, and oil and grease was 80%, 75% y 95 % .The overall efficiency of the treatment units provided good quality effluent.